Ethics and public administration: On the Italian case and beyond - Giovanola, Benedetta (2011)
In Italy the theme of ethics and public administration has not yet found expression in a shared ethical-normative perspective and a systematic regulative framework that might help to formulate suitable principles and promote good practices. The present contribution will first provide an overview of the Italian situation, and then show the need for a philosophical foundation of the relationship between ethics and public administration. Following this theoretical foundational reflection, it will then analyze the applicative and practical aspect of the relationship, by highlighting the importance of the virtue of integrity, and the praxis of communication. - Reproduced.
Keywords: Public administration - Italy:Ethics - Itlay; Public administration